Instrumental Reasoning and Systems Methodology: An Epistemology of the Applied and Social Sciences. - Burns, Thomas J. (The Accounting Review, 1981)
Reviews the book "Instrumental Reasoning and Systems Methodology: An Epistemology of the Applied and Social Sciences," by Richard Mattessich.